Board Structure, Ownership Structure and Firm Performance: A Study of New Zealand Listed-Firms - Fitriya Fauzi; Stuart Locke (Asian Academy of Management Journal of Accounting and Finance, 2012)
This paper investigates the role of board structure and the effect of ownership structures on firm performance in New Zealand’s listed firms. Several studies, the majority from the U.S.A, U.K. and Japan, have examined the relationship between corporate governance mechanisms, ownership structure and firm performance. Those studies yielded different results, affected by the nature of the prevailing governance system for each country. Investigating New Zealand’s listed firms could enhance the diversity of the growing body of work that examines this relationship. Though the majority of studies only tested a linear relationship between variables, a number of studies have found a non-linear relationship between board structures, ownership structures and firm performance, and this study confirms the non-linear relationship. Using a balanced panel of 79 New Zealand listed firms, this study employs a Generalised Linear Model (GLM) for robustness. The result reveals that board of directors, board committees, and managerial ownership have a positive and significant impact on firm performance. Meanwhile, non-executive directors, female directors on the board and blockholder ownership lower New Zealand firm performance.